2005
DOI: 10.1149/1.1943667
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Small Amounts of Impurities on Initial Oxidation of Copper at 400 and 800°C in 0.1 MPa Oxygen Atmosphere

Abstract: To investigate the influence of small amounts of impurities on the initial oxidation of copper, copper oxidation was carried out at 400 and 800°C in 0.1 MPa oxygen atmosphere by using 99.5% ͑2 N͒ and 99.9999% ͑6 N͒ pure specimens. Oxidation of 6 N copper at 400°C for 60 s showed that the number density of Cu 2 O oxide islands beneath the thin CuO layer varied with the face of copper crystals, and the nucleation of Cu 2 O occurred preferentially at grain boundaries. At an elevated temperature of 800°C, nucleati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…[27] The various data reported by different authors might be related to the measurement methods they adopted. [21,28,29] For that reason, this study verifies the fraction of CuO at 350°C to 1050 °C using a direct and reliable metallographic method. Figure 5 shows typical cross-sections of double-layered scales on FZR copper oxidized at 1000 °C, 800 °C, 600 °C, and 400 °C under 0.1 MPa oxygen pressure.…”
Section: A Oxidation Mechanism Of Copper In 01 Mpa Oxygen At 350 °Cmentioning
confidence: 58%
“…[27] The various data reported by different authors might be related to the measurement methods they adopted. [21,28,29] For that reason, this study verifies the fraction of CuO at 350°C to 1050 °C using a direct and reliable metallographic method. Figure 5 shows typical cross-sections of double-layered scales on FZR copper oxidized at 1000 °C, 800 °C, 600 °C, and 400 °C under 0.1 MPa oxygen pressure.…”
Section: A Oxidation Mechanism Of Copper In 01 Mpa Oxygen At 350 °Cmentioning
confidence: 58%
“…5a, after heating Cu foil in high purity Argon flow, some clusters of 500-1000 nm remain mainly at the Cu crystal boundaries as well as a minority of the Cu crystal surface. 33 The EDS mapping of the O element in Fig. 5b (EDS spectroscopy of individual spots is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent papers [4][5][6][7][8][9][10] revealed that the oxidation activation energies of Cu were very different as reviewed in Table 1. As can be seen that the value of oxidation activation energy at 623-823 K for OFHC Cu [7] is 84 kJ/mol, which is higher than that of 52 kJ/mol for a 2N Cu [9] and 40 kJ/mol for a floating zone refined Cu [9][10] a 6N Cu [10].…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen that the value of oxidation activation energy at 623-823 K for OFHC Cu [7] is 84 kJ/mol, which is higher than that of 52 kJ/mol for a 2N Cu [9] and 40 kJ/mol for a floating zone refined Cu [9][10] a 6N Cu [10]. Thus, it has to consider the effect of the impurity on the OR of Cu.…”
Section: Introductionmentioning
confidence: 99%